Competitive and timely food supply combined with operational risk. Issue 1 (2nd January 2017) - Voldrich, Simone; Wieser, Philippe; Zufferey, Nicolas
ABSTRACT: The food industry is facing increasing pressures with issues of food safety, waste and sustainable development for a growing population, while using limited resources. We propose a methodology that combines processing time and cost (PTC) with operational risk (ORk) to address these challenges while considering economic interest of each player in the supply chain environment. Quantitative results from a global food company are presented, which show that the joint analysis of PTC and ORk, in contrast with each of the single objective approaches, results in quantifiable, tangible insights for actual practice. The step-by-step optimisation enables each player to reconfigure its activities for competitive advantage.